Prevalence and Clinicopathological Features of Triaditis in a Prospective Case Series of Symptomatic and Asymptomatic Cats. (14th June 2016) - Fragkou, F.C.; Adamama‐Moraitou, K.K.; Poutahidis, T.; Prassinos, N.N.; Kritsepi‐Konstantinou, M.; Xenoulis, P.G.; Steiner, J.M.; Lidbury, J.A.; Suchodolski, J.S.; Rallis, T.S.
Abstract : Background: The term triaditis designates the concurrent presence of idiopathic inflammatory bowel disease (IBD), cholangitis, and pancreatitis in cats. Hypothesis/Objectives: The histopathology of concurrent, but often subclinical, inflammatory processes in the small intestine, liver, and pancreas of cats is poorly described. We aimed to investigate the frequency of enteritis, cholangitis, pancreatitis, or some combination of these in symptomatic and asymptomatic cats, compare clinicopathological features, and correlate histopathological with laboratory findings. Animals: Domestic cats (27 symptomatic, 20 asymptomatic, and 8 normal). Methods: Prospective study. Physical examination, laboratory variables (CBC, serum biochemistry profile, serum thyroxine concentration, serum feline trypsin‐like immunoreactivity [fTLI], feline lipase immunoreactivity [fPLI, as measured by Spec fPL ® ], urinalysis, and fecal analysis), imaging, and histopathological examinations were conducted. Feline liver, pancreas, and small intestine were biopsied during laparotomy. Results: Inflammatory lesions were detected in 47 cats (27 symptomatic, 20 asymptomatic). In total, 20 cats had histopathologic lesions of IBD (13/47, 27.7%), cholangitis (6/47, 12.8%), or pancreatitis (1/47, 2.1%) alone, or inflammation involving >1 organ (27/47, 57.4%). More specifically, 16/47 cats (34.0%) had concurrent lesions of IBD and cholangitis, 3/47 (6.4%) of IBD and pancreatitis, and 8/47 cats (17%) of triaditis. Triaditis was identified only in symptomatic cats (8/27, 29.6%). A mild, positive correlation was detected between the severity (score) of IBD lesions and the number of comorbidities (rho = +0.367, P = .022). Conclusions and Clinical Importance: Histopathological evidence of IBD or IBD with comorbidities was detected in both symptomatic and asymptomatic cats. The possibility of triaditis should be considered in symptomatic cats with severe IBD.